Multiple Determinants of Anuran Richness and Occurrence in an Agricultural Region in South-Eastern Brazil - Prado, Vitor H. M. [UNESP]; Rossa-Feres, Denise de C. [UNESP] (Springer, 2014)
In agricultural landscapes, studies that identify factors driving species richness and occupancy are important because they can guide farmers to use conservation practices that minimize species loss. In this context, anurans are threatened by habitat loss because they depend on the characteristics of both local water bodies and adjacent landscapes. We used a model selection approach to evaluate the influence of local and landscape variables in determining anuran species richness and occurrence in 40 freshwater bodies in a heavily deforested region of semideciduous Atlantic Forest in southeastern Brazil. Our aim was to develop recommendations for conservation of anuran communities in rural areas. Pond hydroperiod and area were the most important variables for explaining anuran species richness and occupancy, with greatest species richness being found in water bodies with intermediate hydroperiod and area. Other important variables that reflected individual species occupancies were the number of vegetation types and pond isolation. In addition, recent studies evidenced that water bodies near forest fragments have higher anuran abundance or diversity. In conclusion, we suggest the maintenance of semi-permanent ponds, isolated from large rivers or reservoirs and near forest fragments, as an effective strategy to conserve anuran fauna in agricultural landscapes of southeastern Brazil. Brazilian government requires the maintenance of forests as legal reserve in each farm, and farmers need to maintain ponds as drinking water for cattle or crop irrigation. For this reason, the guidelines suggested in the present study can be easily adopted, without additional costs to rural productivity.
Keywords: Amphibian; Generalized linear mixed model; Community ecology; Landscape; Wildlife management; Environmental quality